Analyze and Record a Series of Corporate Sales Transactions On Web Based Accounting Online System - Djatmiko, M Budi; Husain, Al; Maulani, Giandari; Nirmalasari, Leli (Pandawan, 2017)
In the economic activities of the company can not be separated from the name of the process of sales and purchases. Especially in the company's accounting system sales process does not escape become part of the system. That's because sales become vital to prosper the company's welfare. As a financial revenue source in the company the sales process must be analyzed and recorded in real time whether wherever and whenever. As an anticipatory action to reduce the crime of financial acts such as manipulation at the company so as not to cause big losses to the company and result in bankruptcy of the company. Use of Web Based Accounting Online System or commonly known WBAOS it can all be done easily. Starting from analyzing company sales to record sales. This is considered very effective if using an accounting system that is still offline and more efficient of course.